2021
DOI: 10.3390/pr9122150
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Optimization and Control Techniques for Intensifying Processes

Abstract: Process Intensification (PI) is a vast and growing area in Chemical Engineering, which deals with the enhancement of current technology to enable improved efficiency; energy, cost, and environmental impact reduction; small size; and better integration with the other equipment. Since process intensification results in novel, but complex, systems, it is necessary to rely on optimization and control techniques that can cope with such new processes. Therefore, this review presents some advancements in the field of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 136 publications
0
13
0
Order By: Relevance
“…The purpose of the quality control loop is to maintain the desired product purities. In this work, temperature control is adopted since it allows effective inferential composition control and is commonly used in the industry. , The composition control is not used given its higher costs and low reliability caused by the longer dead time. , Before installation of the temperature control loops, the location of the temperature-sensitive tray in each column must be identified. Some common selection methods include the open-loop sensitivity analysis, slope criterion, and singular value decomposition criterion .…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of the quality control loop is to maintain the desired product purities. In this work, temperature control is adopted since it allows effective inferential composition control and is commonly used in the industry. , The composition control is not used given its higher costs and low reliability caused by the longer dead time. , Before installation of the temperature control loops, the location of the temperature-sensitive tray in each column must be identified. Some common selection methods include the open-loop sensitivity analysis, slope criterion, and singular value decomposition criterion .…”
Section: Methodsmentioning
confidence: 99%
“…8 The remaining 103 studies were related to the design and control of extractive distillation for the separation of azeotropic mixture, where 79 studies focused entirely on the steady-state design, while the remaining 27 involved control studies. A detailed literature review covering these studies has been presented in our previous reviews for binary 9 and ternary 10 azeotropic mixtures. A further breakdown of the 79 design studies revealed that the majority (about 65 studies) focused on conventional extractive distillation, while only about 14 studies worked on intensified extractive distillation, 11 such as side-stream (SS), [12][13][14] thermally coupled (THC), [15][16][17] dividing-wall column (DWC), 18,19 heat pump (HP), 20,21 and heat-integration (HI); 22 the summary of is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The second contribution of this work is to explore the possibility of improving the energy consumption and TAC through process optimization, which was proven to reduce the energy consumption efficiently and lower the environmental emission, as evident in a handful number of recent studies for reactive or extractive-based distillation. , In this work, the double-column reactive-extractive distillation (DCRED) with a preconcentration column consists of various types of decision variables, such as discrete or continuous, which translate to a mixed integer nonlinear programming (MINLP) problem that cannot be effectively handled using the sequence quadratic programming (SQP) optimization method or the traditional SI as employed in most of the existing studies (Table ). Various stochastic optimization algorithms have been devised to overcome this issue, such as the nondominated sorting genetic algorithm (NSGA), , mesh adaptive direct search (MADS) algorithm, and particle swarm optimization (PSO), to tackle these MINLP problems.…”
Section: Introductionmentioning
confidence: 99%